How Much is Stable the Bonding of CAD-CAM Implant-Supported All-Ceramic Restorations to Titanium Bases Clinically? A Systematic Review - Shadid RM (Clinical, Cosmetic and Investigational Dentistry)
Rola Muhammed Shadid1,2 1American Board of Oral Implantology; Faculty of Dentistry, Arab American University, Jenin, Palestine; 2Private Practice, Jenin, PalestineCorrespondence: Rola Muhammed Shadid, Department of Prosthodontics, Faculty of Dentistry, Arab American University, P.O Box: 240, Jenin, Palestinian Territory, Tel +00970594494066, Email rola.shadid@aaup.eduAbstract: The rapid advancement of digital technologies and the introduction of new ceramic materials have largely attributed to the notable transition from metal-ceramic to all-ceramic implant restorations bonded to Ti-bases. The purpose of this review was to evaluate all clinical studies reporting on the bond stability between CAD-CAM implant-supported all-ceramic restorations and Ti-bases. The review was directed according to the PRISMA guidelines to answer the focused question “How much is the stability and durability of the resin bond between implant-supported fixed CAD-CAM ceramic restorations and Ti- bases clinically?”. The PubMed, Google Scholar, and Cochrane databases were investigated to identify related clinical studies. Human studies assessing at least 10 patients restored with implant-supported fixed CAD-CAM ceramic restorations luted to prefabricated Ti-bases with a mean follow-up of at least 1 year and published in an English-language up to Sep. 2024 were included. The restorations could be single crown, fixed dental prosthesis, or full-arch fixed prosthesis. The search yielded 5,190 records; of these, 59 full-text articles were evaluated based on eligibility criteria. Ultimately, 40 studies were included. All 40 studies demonstrated low debonding rates from Ti-bases for single copings, multi-unit fixed dental prostheses, and full arch zirconia prostheses. Based on the limited evidence available, different factors were blamed for the debonding incidence, such as Ti-base height, geometry, luting agent, inadequacy of passive fit and biomechanical patient- and prosthesis-related factors. CAD-CAM implant-supported all-ceramic restorations bonded to Ti-bases demonstrated relatively high bond stability during observation period ranging from 1 to 7.5 years. More well-designed clinical research with long-term observation periods is highly recommended.Keywords: dental implant, bond stability, Ti-base, ceramic restoration, debonding